2021
DOI: 10.1080/21614083.2020.1862981
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a pedagogic course in a CPD programme for paediatricians at out-patient clinics

Abstract: Equipping paediatricians for the challenges of the explosive development of knowledge and specialised health care calls for a well-planned continuing professional development (CPD) strategy which updates paediatric competencies and the pedagogic skills among paediatricians. The purpose of the study was to evaluate the effects of a pedagogic course, integrated into a CPD programme for paediatricians at outpatient clinics. The pedagogic course comprised three learning components, participation in a CPD programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Six of the participants contributed to the main programme as educators in the role of subject‐matter specialists, and six participants completed the optional pedagogic assignment at their own clinics. The embedded pedagogic course with the emphasis on the pedagogic assignment has been reported in a separate paper 16 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six of the participants contributed to the main programme as educators in the role of subject‐matter specialists, and six participants completed the optional pedagogic assignment at their own clinics. The embedded pedagogic course with the emphasis on the pedagogic assignment has been reported in a separate paper 16 …”
Section: Resultsmentioning
confidence: 99%
“…The learning strategy of the embedded pedagogic course was formulated according to the case discussions used throughout the programme. 16,26 The results of the participants' evaluations of the 'embedded pedagogic course' indicated that the participants were able to take in and apply the adult pedagogic principles utilised during the programme in a way that was highly appreciated by their co-workers. This therefore suggests that it is possible to reach out to enhance the learning environment at the participants' workplaces by strengthening their educational skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations